ECCENTRIC DOM- CHROMATIC NUMBER OF GRAPHS (International Journal of Food and Nutritional Sciences, 2022)
For a given χ-colouring of a graph a Eccentric dominating set S⊆V(G) is said to be Eccentric dom- Colouring set (γ_edc)if it contains atleast one vertex of each colour class of G. In this paper we establish Eccentric Dom- Chromatic Number of Graphs. In a particular, we investigate Eccentric dom- Chromatic number for star, Path.